Religious studies specification A - Parry, Lesley; Hayes, Jan; Butler, Sheila (Dynamic learning, 2016)
Content covered: - Component 1: The study of religions: beliefs, teaching and practices (through Christianity, Islam and Judaism) - Component 2: Religious, philosophical and ethical themes (themes A, B, C, D,E and F) - Covers the short course content.